THE EFFECT OF EMPLOYEE COMMITMENT, SELF EFFICACY AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. NATURA PLASTINDO - Revanda Putri Aggasi, Vanny; Sumartik, Sumartik; Ubaidillah, Hasan (JURNAL EKBIS, 2025)
This study aims to determine and ensure the influence of job satisfaction, self-efficacy, and employee commitment on employee performance at PT. Natura Plastindo Pasuruan Regency. The methodology of this study is quantitative. The population of the study was employees of PT. Natura Plastindo Pasuruan Regency. All sampling approaches were used to obtain this data. The research sample consisted of fifty-four employees. Respondents were given a survey or questionnaire that was evaluated using a Likert scale to collect primary data for this study. Data were analyzed using statistical approaches and quantitative data analysis tools. Descriptive analysis, t-test, f-test, and multivariate linear regression in addition to hypothesis testing with IBM SPSS 25 software, were statistical test techniques used. The results of the partial test stated that each employee commitment, self-efficacy, and job satisfaction had a positive and significant influence on employee performance. The simultaneous results also stated that employee commitment, self-efficacy, and job satisfaction together had a positive and significant influence on employee performance.